Polymerase chain reaction for detection of some highly dangerous viral fish disease agents - A. S. Tarasova; A. V. Perchun; V. P. Melnikov (Ветеринария сегодня)
Today viral fish diseases cause major losses in the world aquaculture. Pathogen spread often occurs during the transportation of fish from infected farms to the disease-free ones. Therefore, the import of fish stocking material to Russia from countries with a different epidemic situation requires risk-based monitoring and forecasting. Diagnostics is of primary importance in the complex of measures to prevent the spread of viral infections in fish. To date, laboratory diagnostics of viral fish diseases is based on pathogen isolation and its identification using serological methods which require a lot of time and are performed only in large research institutes with specialized laboratories. Molecular diagnostic methods are more sensitive and high-performance. The article presents the results of using reverse transcription polymerase chain reaction to detect a number of highly dangerous viral diseases of fish (Salmonidae). As a result of this work, primers were selected and the temperature and time conditions of the reaction were optimized for the identification of infectious hematopoietic necrosis, viral hemorrhagic septicemia and infectious salmon anemia. The results obtained during the research allowed us to establish that this diagnostic method is highly specific with analytical sensitivity to infectious salmon anemia virus of 2.5 lg TCD50/сm3, to infectious hematopoietic necrosis – 2.9 lg TCD50/сm3 and to viral hemorrhagic septicemia – 4.2 lg TCD50/ сm3. The described method was used to identify reference and field strains available at the FGBI ARRIAH Reference Laboratory for Aquaculture Diseases and isolated in different years in fish farms in the territory of the Russian Federation. The research data correlated with the results obtained from virus neutralization in cell culture and ELISA performed using commercial kits. The proposed method of RT-PCR allows to detect pathogens both in fish with pronounced clinical signs and in latent virus carriers.